The Influence of Education Personnel Competency on Student Academic Service Satisfaction - Raja, Togu Harlen Lbn.; Sitanggang, HD. Melva; Lbn. Raja, Edward A.; Zebua, Adiwima Zebua; Lbn. Raja, John G. (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research aims to determine the extent to which the quality of educators and the quality of educational staff influence student satisfaction with the services they receive at an educational institution. The research method used is a quantitative research approach. The survey and research subjects included 85 education staff and 278 Indonesian Business and Computer Institute students who were randomly selected from the Indonesian Business and Computer Institute. Data was collected through a questionnaire using a Likert scale. To ensure the reliability of the data, validity and reliability tests were carried out, and the results showed that all data followed a normal distribution. The research results reveal that the quality of educators has a significant influence on the level of student satisfaction with the services they receive. Besides that, The quality of educational staff also has a significant influence on the level of student satisfaction with these services. These results confirm that both the quality of educators and the quality of educational staff play an essential role in shaping student perceptions and satisfaction with the services provided by educational institutions. Furthermore, this study also measured the coefficient of determination (R)2, which revealed that the quality of educators and educational staff strongly correlates with student satisfaction with services. In other words, these variables can explain most of the variation in student satisfaction levels. These results highlight the importance of the quality of educators and education personnel in creating an adequate and satisfying educational environment for students.